2009
DOI: 10.1016/j.ecss.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity patterns of free-living marine nematodes in a tropical bay: Cienfuegos, Caribbean Sea

Abstract: a b s t r a c tSpatial and temporal biodiversity patterns of free-living marine nematodes were studied in Cienfuegos Bay, a tropical semi-enclosed basin in the Caribbean Sea. Taxonomic (to species level) and functional (biological trait) approaches were applied for describing the assemblage structure and relating it to abiotic environment based on a sampling scheme in six subtidal stations and three months. Biological trait approach added relevant information to species pattern regarding relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 40 publications
9
44
1
Order By: Relevance
“…Similar outcomes were observed by Schratzberger et al (2007) for nematode assemblages in the North Sea and Armenteros et al (2009) in the Caribbean Sea, where the inclusion of trait-based analyses provided additional information of community distribution patterns regarding different environmental factors. In the present study although the information obtained by the taxonomic approach was not superimposed on that obtained with the functional ones, the distribution patterns of the communities related to similar sets of environmental parameters.…”
Section: Taxonomic Vs Functional Approachessupporting
confidence: 64%
See 1 more Smart Citation
“…Similar outcomes were observed by Schratzberger et al (2007) for nematode assemblages in the North Sea and Armenteros et al (2009) in the Caribbean Sea, where the inclusion of trait-based analyses provided additional information of community distribution patterns regarding different environmental factors. In the present study although the information obtained by the taxonomic approach was not superimposed on that obtained with the functional ones, the distribution patterns of the communities related to similar sets of environmental parameters.…”
Section: Taxonomic Vs Functional Approachessupporting
confidence: 64%
“…The use of biological traits has been strongly encouraged in studies aiming at analysing diversity patterns (Armenteros et al, 2009) and assessing ecosystem functioning (Bremner et al, 2003). In this context, since trait-based approaches are known for their high robustness with decreased taxonomic resolution (Menezes et al, 2010), problems associated with misidentification can be less critical since nematode species with high morphological similarity will most probably share the same trait category.…”
Section: Taxonomic Vs Functional Approachesmentioning
confidence: 99%
“…Although the MI may generally give good results in ecological assessments , Armenteros et al (2009) reported unclear results in Cienfuegos Bay (Caribbean Sea), especially for the interaction of anthropogenic and natural factors. A clear relationship between anthropogenic activity (PLI) and the MI was not found in Lake Varano.…”
Section: Notes On the Eqs Of Lake Varanomentioning
confidence: 99%
“…It is also well known as tolerant to a variety of natural and anthropogenic stressors (e.g. Armenteros et al 2009, Gollner et al 2010, Guilini et al 2012. The physiological and behavioural adaptations of T. longicaudata to poorly oxygenated environments include a low respiratory rate and slow movement (Warwick andGee 1984, Guerrini et al 1998).…”
Section: Effect Of Environmental Variables On Taxonomic Structure Andmentioning
confidence: 99%
See 1 more Smart Citation